ANALYSIS OF IMPLEMENTATION THE THEMATIC INTEGRATED LEARNING SCIENCE IN THE JUNIOR HIGH SCHOOL (SMP) NEGERI 1 TAMBUSAI - Nurhikmah Sasna Junaidi; Afdhal Ridho (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
This study aimed to describe the implementation of thematic integrated science learning at SMP N 1 Tambusai. The research method was quantitative descriptive research. The data used as a result were in the form of filling questionnaire data by teachers. Based on the results, it was found that the planning aspects of the integrated science learning plan with a percentage of 75% was good, the implementation aspect of integrated science learning with a percentage of 72.5% was enough, and aspects of assessment learning process and results with a percentage of 77.5% was good. Thus, the average of whole aspect was 75% categorized as good. So, the implementation of thematic integrated science learning at SMP N 1 Tambusai has been carried out sufficiently, both in accordance with the objectives of the 2013 Curriculum.